2018
DOI: 10.9734/jammr/2018/41278
|View full text |Cite
|
Sign up to set email alerts
|

Stigmatization, Status Disclosure and Support among HIV Positive Women in the Kumasi Metropolis of Ghana; a Qualitative Study

Abstract: Background: HIV-related stigma and discrimination are impediments to mitigating the HIV epidemic, with women mostly affected. This qualitative study explored issues of stigmatization, disclosure of status and adherence to Antiretroviral therapy (ART) among HIV positive women. Methods: This study was conducted in three ART centers in the Kumasi metropolis of Ghana. 23 HIV positive women aged 18-49 years and on Antiretroviral (ARVs) for treatment or prophylaxis for >3 months and 14 health workers at the ART cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
2
0
1
Order By: Relevance
“…Dari hasil penelitian yang sudah dilakukan tersebut membuktikan bahwa persentase diskriminasi masih tinggi di setiap kelompok masyarakat. 9,10,11 Banyak faktor yang mempengaruhi terjadinya diskriminasi terhadap ODHA di masyarakat, salah satunya pengetahuan. Pengetahuan tentang HIV/AIDS mempengaruhi sikap dan perilaku seseorang terhadap ODHA.…”
Section: Pendahuluanunclassified
“…Dari hasil penelitian yang sudah dilakukan tersebut membuktikan bahwa persentase diskriminasi masih tinggi di setiap kelompok masyarakat. 9,10,11 Banyak faktor yang mempengaruhi terjadinya diskriminasi terhadap ODHA di masyarakat, salah satunya pengetahuan. Pengetahuan tentang HIV/AIDS mempengaruhi sikap dan perilaku seseorang terhadap ODHA.…”
Section: Pendahuluanunclassified
“…Transportation is critical for socioeconomic development (Boateng et al, 2022). Hence various forms of infrastructure like airports, seaports, railways, and roads have been constructed to enhance transportation.…”
Section: Introductionmentioning
confidence: 99%
“…Ocran (2022) dealt with structural dimensions of discrimination toward PWDs; Obiri-Yeboah et al (2022) addressed the economic impact of rickshaws; Acheampong and Asabre (2022) studied place-based accessibility and found out that accessibility was poor due to congestion (2022); Boateng et al (2022) 2018) looked at accessibility within the CBD and concluded that there were serious challenges. Kleager (2017) dealt with the risks along the Kumasi-Accra road that resulted in the construction of a bypass to avoid certain towns where accidents had been frequently occurring.…”
Section: Introductionmentioning
confidence: 99%